The Influence of Supervisory Promotion and Network Location on Subordinate Careers in a Dual Ladder RD&E Setting - Katz, Ralph; Tushman, Michael; Allen, Thomas J. (Management Science, 1995)
This longitudinal study examines the impacts of supervisors' promotion paths and gatekeeper status on the career outcomes of technical subordinates in a dual ladder system. Results indicate that project supervisors significantly affect the chances of one's promotion along each track. Professionals reporting to supervisors promoted to the technical ladder were significantly more likely to also be promoted technically, especially in research. On the other hand, professionals reporting to gatekeeping supervisors in development were significantly more likely to be promoted up the managerial ladder. Gatekeeper status was more important in influencing subordinates' communication activities and subsequent promotions than supervisors' promotion path. These results underscore the importance of managing socialization and the career paths of gatekeepers and those reporting to them for enhancing the success of dual ladder reward systems.